2018
DOI: 10.1038/s41467-018-06184-3
|View full text |Cite
|
Sign up to set email alerts
|

Roquin targets mRNAs in a 3′-UTR-specific manner by different modes of regulation

Abstract: The RNA-binding proteins Roquin-1 and Roquin-2 redundantly control gene expression and cell-fate decisions. Here, we show that Roquin not only interacts with stem–loop structures, but also with a linear sequence element present in about half of its targets. Comprehensive analysis of a minimal response element of the Nfkbid 3′-UTR shows that six stem–loop structures cooperate to exert robust and profound post-transcriptional regulation. Only binding of multiple Roquin proteins to several stem–loops exerts full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 61 publications
(131 reference statements)
5
57
0
Order By: Relevance
“…An example of a protein with various RBDs recognizing stem‐loop structures on the 3′‐UTR of mRNAs is the ring finger and CCCH‐type domains 1, also known as Roquin‐1 (Figure a), a protein mediating T helper‐17 cell differentiation . The observation that Roquin‐1 interacts with RNA structural elements on the 3′‐UTR of proinflammatory cytokines like tumor necrosis factor (TNF) and interleukin‐6 (IL‐6), allowed the identification of novel protein partners by searching RNAs that fold into similar stem‐loops .…”
Section: Relevance Of Rna Structure For Rbp Recognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…An example of a protein with various RBDs recognizing stem‐loop structures on the 3′‐UTR of mRNAs is the ring finger and CCCH‐type domains 1, also known as Roquin‐1 (Figure a), a protein mediating T helper‐17 cell differentiation . The observation that Roquin‐1 interacts with RNA structural elements on the 3′‐UTR of proinflammatory cytokines like tumor necrosis factor (TNF) and interleukin‐6 (IL‐6), allowed the identification of novel protein partners by searching RNAs that fold into similar stem‐loops .…”
Section: Relevance Of Rna Structure For Rbp Recognitionmentioning
confidence: 99%
“…Subsequently, characterization of RNA reporters carrying these sequences revealed that RNA stability is governed by Roquin‐1. Like other RBPs, Roquin‐1 is a versatile protein recognizing not only stem‐loop structures but also linear pyrimidine‐rich sequences . Roquin‐1 shares RNA targets with Regnase‐1, a protein repressing translation of mRNAs encoding factors involved in Th1 differentiation via structural elements within their 3′‐UTRs .…”
Section: Relevance Of Rna Structure For Rbp Recognitionmentioning
confidence: 99%
“…E3 ubiquitin-protein ligase Roquin, belongs to the Roquins which are a family of highly conserved RNA-binding proteins involved in ubiquination, are crucial for T-cell-dependent B-cell responses (Athanasopoulos et al, 2016) and play important roles in modulating Tcell activity (Akef and Muljo, 2018). Roquins repress constitutive decay elements containing mRNAs and play a critical role in RNA homeostasis and immunological self-tolerance Essig et al, 2018;Mino and Takeuchi, 2018). Roquin plays multifaceted roles both in the generation of a homeostatic immune response, as well as during chronic inflammation and autoimmunity (Schaefer and Klein, 2016;Lee et al, 2019).…”
mentioning
confidence: 99%
“…Most of the above‐mentioned studies focus on the function of RBPs in immune cells. However, recent pioneering studies have revealed that these RBPs appear to be multifunctional in order to achieve the proper mounting of immune responses in specific milieu . Thus, future studies will be necessary to integrate the role of RBPs in individual cell populations at the organismal level.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, via genome‐wide identification of Roquin target mRNAs, Roquin has been demonstrated to bind to CDEs, which canonically form triloop stem‐loop structures . In addition to this structure, recent reports using systematic evolution of ligands by exponential enrichment (SELEX) and photoactivatable ribonucleoside‐enhanced cross‐linking and immunoprecipitation (PAR‐CLIP) methods have shown that Roquin‐1 also recognises noncanonical hexaloop structures and linear binding elements (LBEs), respectively . Thus, our understanding of cis‐elements remains incomplete and further studies are necessary to comprehensively identify and validate potential RBP binding sites.…”
Section: Inflammation‐related Mrnas Are Regulated By a Set Of Rna Binmentioning
confidence: 99%